Socioeconomic inequalities in Chile during the COVID-19 pandemic: A regional analysis of income poverty - Iris Delgado; Sushma Dahal; Maria I. Matute; Paola A. Rubilar Ramírez; Svenn-Erik Mamelund; Gerardo Chowell (PLoS ONE, 2025)
The COVID-19 pandemic caused an unprecedented economic crisis, intensifying poverty levels in Latin America, particularly in Chile. This study examines the short- and long-term socioeconomic impacts of COVID-19 on income poverty in Chile, focusing on regional disparities, rurality, ethnicity, educational attainment, and immigration. Using data from the Chile National Socioeconomic Characterization Survey (CASEN) for 2017, 2020, and 2022, we analyzed poverty trends across the pre-pandemic, pandemic, and post-pandemic periods. We employed spatial clustering techniques with Local Moran’s I to detect poverty hotspots and applied logistic regression models to identify key sociodemographic factors associated with these hotspots. Our results reveal stark regional disparities, with disproportionately higher poverty rates among rural populations, Indigenous communities, and individuals with lower education levels or immigrant backgrounds. The proportion of individuals in poverty hotspots rose from 6.8% in 2017 to 8.6% in 2020, before slightly declining to 7.7% in 2022. Although emergency monetary subsidies helped reduce overall poverty from 10.8% in 2020 to 6.5% in 2022, these measures were insufficient to address deep-rooted structural inequalities. Our findings underscore the urgent need for targeted, long-term policies that go beyond temporary financial assistance and tackle systemic disparities linked to rurality, ethnicity, education, and immigration. Such measures are essential for achieving sustainable poverty reduction and fostering inclusive economic growth in Chile.